The Variation of Functional Traits in Leaves and Current-Year Twigs of Quercus aquifolioides Along an Altitudinal Gradient in Southeastern Tibet - Zhang, Xinsheng; Wang, Chao; Zhou, Chenni (Frontiers in Ecology and Evolution, 2022)
Clarifying the adaptation mechanism of alpine plants to climate or habitat under the alpine environmental gradient on the Qinghai–Tibet Plateau is substantially important to protect the alpine plant germplasm resources. In this study, the spatial distribution characteristics of functional traits of 180 leaves and 108 current-year twigs of Quercus aquifolioides on five altitudinal gradients suitable for single species’ in Southeastern Tibet were analyzed. The relationship between the functional traits and habitat factors (topographic and soil factors) was also explored. Key results: the functional traits of leaves and current-year twigs of Q. aquifolioides in Southeastern Tibet showed significant linear variations along the altitude gradients suitable for the distribution of this single species (p< 0.001). Q. aquifolioides at low altitudes tended to have shorter current-year twigs and less leaves with larger LA and higher RWC than Q. aquifolioides at high altitudes. Strong trade-off and coordination relationship were found between the functional traits of leaves and those of current-year twigs, respectively. Principal component analysis showed that LA and SLA contributed the most to the leaf traits, while twig dry weight and Huber value contributed the most to the functional traits of current-year twigs. SL(slope gradient) and TN contributed the most to leaf functional traits and had significant correlation (p< 0.05); AL(altitude) was the main determinant of functional traits in current-year twigs of Q.aquifolioides in southeast Tibet. The ecological adaptation strategy of Q.aquifolioides was formed through the trade-off mechanism among various functional traits to adapt to the changes of hydrothermal conditions and soil environmental factors caused by altitude gradient in the alpine region.